Gold Medal for Finnish Health in All Policies Book - Ray Lewis; Vahid Yazdi Feyzabadi (Kerman University of Medical Sciences, 2014)
This article is a review of the book "Health in All Policies: Seizing opportunities, implementing policies" edited by Kimmo Leppo, Eeva Ollila, Sebastián Peña, Matthias Wismar, and Sarah Cook. This book (printed and online publication) was published by the Finnish Ministry of Social Affairs and Health, Finland in 2013 (1). The book is freely available at http://www.euro.who.int/__data/assets/pdf_file/0007/188809/Health-in-All-Policies-final.pdf. The main features, structure, and highlighted contents of the book are briefly sketched out in this review. The book promotes understanding of a Health in All Policies (HiAP) approach, the history, and the scientific evidence of effectiveness available to apply the HiAP concept in order to overcome challenges faced by policy-makers. HiAP is a relatively novel approach which arises from the traditional idea that health is not only medicine (2). The book offers lessons to policy-makers and managers on how to apply the HiAP approach. It further highlights the health sector's role in developing healthy public policies. In addition, the book provides examples of structures to foster collaboration, coherence, and participation among stakeholders from different government portfolios and responsibilities. The book further provides invaluable insights for politicians, researchers, and civil society advocates.